1978
DOI: 10.1002/ar.1091910304
|View full text |Cite
|
Sign up to set email alerts
|

Development of adrenergic innervation of the iris and fluorescent ganglion cells in the choroid of the chick eye

Abstract: The developing innervation of the chick eye has been studied using catecholamine histofluorescence. The innervation of the pupillary dilator by the superior cervical ganglion begins on day 13 of incubation when fluorescent axons can be seen in the ciliary zone circumscribing the dilator. On day 14 a few processes are seen to branch from this band into the dilator. The number of processes in the dilator increases on days 15 and 16. After day 16 there is a reorganization of the fibers radially accompanied by a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…VMAT2 has an affinity for serotonin, dopamine, nor-adrenaline, and adrenaline (Peter et al 1994), and so, cannot be used as an exclusion marker. In fact, early studies of sympathetic innervation of the chicken eye were based on fluorescence-histochemical methods that did not discriminate between the different catecholamines (Ehinger 1967; Guglielmone and Cantino 1982; Kirby et al 1978); therefore, it is unknown which catecholamines are used by the sympathetics in chicken eyes. Although it remains possible that the absence of DBH labeling in the chick eye could be due to antigen incompatibility, it is possible that the chick system using dopamine or serotonin instead of noradrenaline, in regulation of the homeostasis of the posterior uvea (Ohngemach et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…VMAT2 has an affinity for serotonin, dopamine, nor-adrenaline, and adrenaline (Peter et al 1994), and so, cannot be used as an exclusion marker. In fact, early studies of sympathetic innervation of the chicken eye were based on fluorescence-histochemical methods that did not discriminate between the different catecholamines (Ehinger 1967; Guglielmone and Cantino 1982; Kirby et al 1978); therefore, it is unknown which catecholamines are used by the sympathetics in chicken eyes. Although it remains possible that the absence of DBH labeling in the chick eye could be due to antigen incompatibility, it is possible that the chick system using dopamine or serotonin instead of noradrenaline, in regulation of the homeostasis of the posterior uvea (Ohngemach et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The sympathetic innervation of the choroid comes from the superior cervical ganglion (Kirby et al, 1978; Guglielmone and Cantino, 1982; Bill, 1985). These noradrenergic neurons terminate on the blood vessels and mediate vasoconstriction.…”
Section: Structure and “Classical” Functions Of The Choroidmentioning
confidence: 99%
“…Since TH and DBH, in particular if co-localised, can be considered specific markers for adrenergic neurons also in birds (Yurkewicz et al 1981;Moons et al 1995), these findings indicate that ICN are innervated by sympathetic postganglionic neurons. The source of sympathetic innervation to the eye is located in the superior cervical ganglion, in birds and in mammals (Kirby et al 1978;Guglielmone and Cantino 1982;ten Tuscher et al 1994). We have previously demonstrated that, from extrinsic sources supplying the eye in Cairina moschata (pterygopalatine, ciliary, and superior cervical ganglia), TH-immunoreactive neurons are only detectable by immunohistochemistry in the superior cervical ganglion (Schrödl et al 2000).…”
Section: General Considerationsmentioning
confidence: 99%